Petrophysics : theory and practice of measuring reservoir rock and fluid transport properties - Tiab, Djebbar (Knovel Library., 2004)
The petroleum geologist and engineer must have a working knowledge of petrophysics in order to find oil reservoirs, devise the best plan for getting it out of the ground, then start drilling. This book offers the engineer and geologist a manual to accomplish these goals, providing much-needed calculations and formulas on fluid flow, rock properties, and many other topics that are encountered every day. New updated material covers topics that have emerged in the petrochemical industry since 1997. * Contains information and calculations that the engineer or geologist must use in daily activities to find oil and devise a plan to get it out of the ground * Filled with problems and solutions, perfect for use in undergraduate, graduate, or professional courses * Covers real-life problems and cases for the practicing engineer.